PENGARUH STATUS GIZI, AKTIVITAS FISIK DAN RIWAYAT KESEHATAN TERHADAP KEBUGARAN JASMANI LANSIA DI PANTI SOSIAL TRESNA WERDHA SABAI NAN ALUIH SICINCIN: THE INFLUENCE OF NUTRITIONAL STATUS, PHYSICAL ACTIVITY, AND HEALTH HISTORY ON PHYSICAL FITNESS IN THE ELDERLY AT TRESNA WERDHA SABAI NAN ALUIH SICINCIN SOCIAL HOME - Fadilla, Azzahla; Welis, Wilda; Rifki, Muhammad Sazeli; Muchlis, Arif Fadli (Jurnal IKEOR, 2026)
Abstract: This study aims to examine the impact of nutritional status, physical activity levels, and health history on physical fitness among older adults at the Tresna Werdha Sabai Nan Aluih Sicincin Social Welfare Home. The method used in this study is a quantitative approach with a cross-sectional design. The study sample consisted of older adults selected using purposive sampling. Data were collected by measuring Body Mass Index (BMI), the Physical Activity Scale for the Elderly (PASE), the Self-Reporting Questionnaire (SRQ), and the Senior Fitness Test (SFT) to assess physical fitness. Data analysis was performed using multiple linear regression. The results of this study indicate that, collectively, nutritional status, physical activity, and health history have a significant impact on the physical fitness of older adults. When considered separately, the level of physical activity has the most dominant impact compared to nutritional status and health history. Therefore, appropriate measures are needed to improve the quality of life of older adults. Keywords: nutritional status, physical activity, health history, physical fitness, older adults